2018
DOI: 10.3892/or.2018.6755
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of glucose‑6‑phosphate dehydrogenase by microRNA‑1 inhibits the growth of pituitary tumor cells

Abstract: Pituitary tumors are generally intracranial neoplasms with high incidence and mortality rates. The investigation of novel factors involved in the tumorigenesis of pituitary tumors and the characterization of the underlying molecular mechanisms is urgently required for the diagnosis and treatment of pituitary tumors. Accumulating evidence has indicated that microRNAs (miRs) serve important roles in the initiation and progression of cancer. The present study found that miR-1 was significantly downregulated in pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Several rate-limiting enzymes such as GLUT1, HK2, PFK1 and G6PD play crucial roles during these glucose metabolism processes (27). Previous studies have shown that these enzymes are regulated directly or indirectly by miRNAs (28)(29)(30)(31)(32). The present results indicated that the expression levels of these enzymes were decrease by miR-218 in NSCLC cell lines.…”
Section: Discussionsupporting
confidence: 58%
“…Several rate-limiting enzymes such as GLUT1, HK2, PFK1 and G6PD play crucial roles during these glucose metabolism processes (27). Previous studies have shown that these enzymes are regulated directly or indirectly by miRNAs (28)(29)(30)(31)(32). The present results indicated that the expression levels of these enzymes were decrease by miR-218 in NSCLC cell lines.…”
Section: Discussionsupporting
confidence: 58%
“…However, why and how G6PD was downregulated in DM rats remains unclear. Some researchers reported in other pathology models and pointed out that the causes of G6PD deficiency or downregulation mainly included four factors: DNA methylation, 33 histone deacetylation, 5,34 alteration in miRNA expression, 35,36 and DNA damage. 37 So, the upstream mechanism of G6PD deficiency or downregulation in diabetic neuropathic pain needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EDTA, NADPH and G6P favor disruption of the dimer, whereas NADP + or certain metal ions favor the tetramer [14]. Additionally, the substrate-binding site and the dinucleotide-binding fingerprint are conserved in human G6PD with the sequences RIDHYLGKE (residues 198-206) and GxxGGDLA (residues [38][39][40][41][42][43][44], respectively [17].…”
Section: Characteristics Of G6pdmentioning
confidence: 99%